A checklist of chigger mites (Acariformes: Trombiculidae) of Southeast Asia - Stekolnikov, Alexandr A. (Zootaxa, 2021)
Chigger mites (Acariformes: Trombiculidae) of Southeast Asia, including Myanmar, Malaysia, Brunei, Singapore, Indonesia, Thailand, Cambodia, Vietnam, and the Philippines have been revised based on reference data and examination of type materials in European collections of chiggers. For 450 species of 49 genera synonymy, collection data on types, lists of known host species and lists of countries are given. The lists of hosts include in total 649 valid species and subspecies of mammals, birds, reptiles, amphibians, and arthropods. Two new synonyms were established: Doloisia (Doloisia) Oudemans, 1910 (= Doloisia (Trisetoisia) Vercammen-Grandjean, 1968, syn. nov.) and Gahrliepia lui Chen and Hsu, 1955 (= Gahrliepia (Gateria) octosetosa Chen, Hsu and Wang, 1956, syn. nov.). Twenty-seven new combinations were proposed: Walchia (Ripiaspichia) biliranensis (Brown, 1997), comb. nov., Walchia (Ripiaspichia) huberti (Upham and Nadchatram, 1968), comb. nov., Walchia (Ripiaspichia) parmulaseta (Brown, 1997), comb. nov., and Walchia (Ripiaspichia) serrata (Brown and Goff, 1988), comb. nov., transferred from Gahrliepia Oudemans, 1912; Farrellioides consuetum (Womersley, 1952), comb. nov. (originally in Trombicula Berlese, 1905), Farrellioides nakatae (Nadchatram and Traub, 1964), comb. nov. (originally in Leptotrombidium Nagayo, Miyagawa, Mitamura and Imamura, 1916), and Farrellioides striatum (Nadchatram and Traub, 1964), comb. nov. (originally in Leptotrombidium), transferred from Euschoengastia Ewing, 1938; Guntheria (Phyllacarus) bushlandi (Philip, 1947), comb. nov. (originally in Ascoschoengastia Ewing, 1946), transferred from Guntherana Womersley and Heaslip, 1943 (syn. of Guntheria Womersley, 1939); Kayella masta (Traub and Sundermeyer, 1950), comb. nov. (originally in Ascoschoengastia), transferred from Cordiseta Hoffmann, 1954; Neoschoengastia stekolnikovi (Kalúz, 2016), comb. nov., transferred from Hypogastia Vercammen-Grandjean, 1967; Susa chiropteraphilus (Brown, 1997), comb. nov., Susa masawanensis (Brown, 1998), comb. nov., and Susa palawanensis (Brown and Goff, 1988), comb. nov., transferred from Cheladonta Lipovsky, Crossley and Loomis, 1955; Ericotrombidium cosmetopode (Vercammen-Grandjean and Langston, 1971), comb. nov., transferred from Leptotrombidium; Eutrombicula gigarara (Brown, 1997), comb. nov., transferred from Siseca Audy, 1956; Microtrombicula eltoni (Audy, 1956), comb. nov., transferred from Eltonella Audy, 1956; Trombiculindus alethrix (Traub and Nadchatram, 1967), comb. nov., Trombiculindus cuteanum (Vercammen-Grandjean and Langston, 1976), comb. nov., Trombiculindus frondosum (Traub and Nadchatram, 1967), comb. nov., Trombiculindus hastatum (Gater, 1932), comb. nov., Trombiculindus lepismatum (Traub and Nadchatram, 1967), comb. nov., Trombiculindus limi (Traub and Nadchatram, 1967), comb. nov., Trombiculindus maxwelli (Traub and Nadchatram, 1967), comb. nov., Trombiculindus roseannleilaniae (Brown, 1992), comb. nov., Trombiculindus sarisatum (Traub and Nadchatram, 1967), comb. nov., Trombiculindus vanpeeneni (Hadi and Carney, 1977), comb. nov., and Trombiculindus yooni (Traub and Nadchatram, 1967), comb. nov., transferred from Leptotrombidium.